Curcumin inhibits cellular cholesterol accumulation by regulating SREBP-1/caveolin-1 signaling pathway in vascular smooth muscle cells - Yuan Hao-yu; Kuang Shuang-yu; Zheng Xing; Ling Hong-yan; Yang Yun-Bo; Yan Peng-Ke; Li Kai; Liao Duan-Fang (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the protective effect and the possible mechanism of curcumin on anti-atherosclerosis. Methods: Morphological changes of atherosclerotic lesions taken from apoE knockout (apoE−/−) mice were determined by hematoxylin–eosin staining. Intracellular lipid droplets and lipid levels were assayed by oil red O staining and HPLC. The protein expression of caveolin-1 was quantified by Western blotting. Translocation and the expression of sterol response element-binding protein-1 (SREBP-1) were indirectly detected by an immunofluorescence analysis. Results: The administration of 20 mg·kg−1·d−1 curcumin to apoE−/− mice for 4 months induced a 50% reduction of atherosclerotic lesions and yielded a 5-fold increase in the caveolin-1 expression level as compared to the model group. Rat vascular smooth muscle cells (VSMC) pretreated with 50 mg·L−1 ox-lipid density lipoprotein(ox-LDL) for 48 h increased cellular lipid contents, and stimulated SREBP-1 translocation, but decreased the caveolin-1 expression level. Lipid-loaded cells exposed to curcumin at various concentrations (12.5, 25, and 50 μmol·L−1) for different durations (0, 6, 12, 24, and 48 h) significantly diminished the number and area of cellular lipid droplets, total cholesterol, cholesterol ester, and free cholesterol accompanying the elevation of the caveolin-1 expression level (approximately 3-fold); the translocation of SREBP-1 from the cytoplasm to the nucleus was inhibited compared with the models. Lipid-loaded VSMC exposed to N-acetyl-Leu-Leu-norleucinal, a SREBP-1 protease inhibitor, showed increased nuclear translocation of SREBP-1, reduced caveolin-1 expression level, and upregulated cellular lipid levels. Conclusion: Curcumin inhibits ox-LDL-induced cholesterol accumulation in cultured VSMC through increasing the caveolin-1 expression via the inhibition of nuclear translocation of SREBP-1.